Investigating Renal Dysfunction and Dyslipidemia in Obese and Overweight Children: Renal Dysfunction and Dyslipidemia in Obese and Overweight Children - Olang, Beheshteh; Fatollahierad, Shiva; Hajipour, Mahmoud; Hosseini, Amirhossein; Fazeli Farsani, Zahra; Sayyari, Aliakbar (Journal of Pediatric Nephrology, 2024)
Background and Aim: Childhood obesity and chronic kidney disease (CKD) are both substantial public health concerns. Obesity is known to contribute directly and indirectly to the development of CKD. This study evaluates kidney damage related to obesity and metabolic comorbidities in overweight and obese children. Methods: A prospective cross-sectional study was conducted in the Obesity Clinic of a Children’s Hospital in Iran from 2017 to 2020 on obese and overweight children aged 2 to 18 years. Biochemical parameters, such as total cholesterol, high-density lipoprotein (HDL), lowdensity lipoprotein (LDL), triglyceride (TG), creatinine, estimated glomerular filtration rate and fasting glucose were measured. A binary logistic regression was used to assess the association between body mass index (BMI) Z-score and biochemical parameters. Two-sided P<0.05 was considered significant. Results: The participants exhibited a mean BMI Z-score of 2.39±0.70. The prevalence of obesity was 78.6% among boys and 52.9% among girls. Additionally, 78.9% of them had an estimated glomerular filtration rate of less than 90 mL/min/1.73 m2. Impaired fasting glucose was present in 15.6% of the participants, while hypercholesterolemia was noted in 66.7% of them. Conclusion: Significant percentages of overweight and obese children have decreased estimated glomerular filtration rate. In addition, dyslipidemia, in the forms of high cholesterol, high TG, and low HDL is found in these children.